2014
DOI: 10.2141/jpsa.0130065
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of <i>Ocimum Gratissimum </i>Improves Immune Response without Affecting the Growth Performance and Blood Characteristics in Taiwan Country Chicken

Abstract: Ocimum gratissimum (OG) was investigated in this study to determine its effect on the immune capability of black-feathered Taiwan country chickens. A total of 90 four-week-old male chickens were randomly assigned to a control group, which was fed with basal diet (BD), and two experimental groups, which were fed with a 0.2 and 0.4 g/kg OG-supplemented BD. During the experimental period, feed intake and body weight were recorded every two weeks to determine growth performance and feed efficiency. Blood was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…In view of ADG, FC chickens significantly grew faster than the others (p<0.05) with 9.34 g/day ( Table 2). The current findings were similar to Pradu Hang Dam chickens (Penmas, 2005), Black Hmong, Black Chinese, Brown Hmong and crossbred Black Hmong  Pradu Hang Dam chickens (Sungkhapreecha et al, 2015) However, some studies revealed greater ADG with the average varied from 16.1 to 54.5 g/day (Castellini et al, 2002;Chen et al, 2014;Leotaragul et al, 2015;Castellini et al, 2016). Due to the factors affect ADG are not only genetic, but also the age of the chicken.…”
Section: Resultssupporting
confidence: 83%
“…In view of ADG, FC chickens significantly grew faster than the others (p<0.05) with 9.34 g/day ( Table 2). The current findings were similar to Pradu Hang Dam chickens (Penmas, 2005), Black Hmong, Black Chinese, Brown Hmong and crossbred Black Hmong  Pradu Hang Dam chickens (Sungkhapreecha et al, 2015) However, some studies revealed greater ADG with the average varied from 16.1 to 54.5 g/day (Castellini et al, 2002;Chen et al, 2014;Leotaragul et al, 2015;Castellini et al, 2016). Due to the factors affect ADG are not only genetic, but also the age of the chicken.…”
Section: Resultssupporting
confidence: 83%
“…Alternatively, higher BKA may have been related to the nutritional quality of the food source available. In addition to proteins, micronutrients, such as vitamin and mineral, are increasingly recognized as critical components of innate immune responses (Chen et al 2014;Ruiz et al, 2010). Stray cats in the low CCA area, such as other urban wildlife, will commonly rely on indirectly provisioned human food sources from garbage or dumpsters.…”
Section: Discussionmentioning
confidence: 99%
“…For this, an increasingly growing interest is focused on the use of natural products such as plant extracts [8] developing future drugs. Ocimum gratissimum (Lamiaceae) is one of the most used plants in traditional medicine in the treatment of several pathologies [9]. Indeed, it has healing, antifungal and anthelmintic properties [10].…”
Section: Introductionmentioning
confidence: 99%